PENERAPAN METODE PEMBELAJARAN KOOPERATIF DALAM MENYONGSONG KURIKULUM 2004 PADA SISWA KELAS 1 SEMESTER II SMP NEGERI10 SURAKARTA TAHUN PELAJARAN 2004/2005 (IMPLEMENTATION OF COOPERATIVE LEARNING METHOD ON FACING THE COMPETENCE BASED CURICULUM (CURICULUM 2004) UPON THE 1st GRADE STUDENT of 2nd SEMESTER OF SMP NEGERI II SURAKARTA IN ACADEMIC YEAR OF 2004/2005) - RUNTUT PRIH UTAMI; ALVI ROSYIDI; SUMANTO SUMANTO (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret, 2006)
The aims of this research are to know the effectiveness of STAD method as one of the cooperative teaching method and compared it with the conventional one. The effectiveness parameters used was the sudent achievement on biology. This research held upon the student of the first grade and of the 2nd semester of SMP Negeri 10 Surakarta in academic year of 2004/2005. Clustered random sampling technique was used upon two classes' i.e the treatment class (using STAD method) and conventional one. Data obtained was then analyzed by t-test. The research concluded that application STAD on facing the curriculum 2004 is a good teaching method. It raised the student's achievement on biology, statistically showed by tobserved> t tabel = 2.039 > 1.670 with significance of 5%.